Improving immunogenicity and effectiveness of influenza vaccine in older adults. (November 2011) - Cao, Weiping; Kim, Jin Hyang; Chirkova, Tatiana; Reber, Adrian J; Biber, Renata; Shay, David K; Sambhara, Suryaprakash
Aging is associated with a decline in immune function (immunosenescence) that leads to progressive deterioration in both innate and adaptive immune functions. These changes contribute to the subsequent increased risk for infectious diseases and their sequelae. Vaccination is the most effective and inexpensive public health strategy for prevention of infection, despite the decreased efficacy of vaccines in older adults due to immunosenescence. The rapid rise in the older adult population globally represents a great challenge for vaccination programs. This article first addresses the status of innate and adaptive immune functions in aging and then focuses on influenza vaccine. The development history of influenza vaccines, current status, and potential strategies to improve the immunogenicity and vaccine effectiveness in older adults are discussed.